Comprehensive genome-wide analysis of the GmFRIGIDA gene family in soybean: identification, characterization, and expression dynamics - Yu, Song; Wang, Yuxuan; Ren, Wenwen; Fang, Yisheng; Wang, Leili; Zhang, Yifei; Song, Chengyang; Luo, Xiao (Frontiers in Plant Science, 2025)
BackgroundFrigida (FRI) genes are crucial for regulating flowering time in plants. While the biological importance of the Frigida-like (FRL) gene family has been recognized in Arabidopsis, a systematic analysis of these genes in soybean is lacking. Characterizing FRL genes in soybean will help uncover their roles in flowering regulation, offering valuable insights for improving soybean adaptation.ResultsIn this study, we identified 16 Frigida genes in soybean, naming them based on their relationship to the FRL genes in Arabidopsis thaliana. These genes are unevenly distributed across thirteen chromosomes. Phylogenetic analysis categorizes Frigida-like proteins from Arabidopsis, soybean, and rice into four distinct subfamilies (I–IV). Our findings indicate that eight GmFRLs arose from whole-genome duplication (WGD) events, alongside two tandem duplication events. Gene structure analysis confirmed that all GmFRL members contain Frigida domains. Additionally, promoter analysis revealed numerous cis-acting elements related to photoperiodic response, suggesting their significant role in soybean’s light response mechanisms. RNA-seq data demonstrated variable expression levels of GmFRL genes across tissues, including flower, leaf, pod, and seed, and other tissues, while subcellular localization and qPCR analyses further support their vital role in light responsiveness in soybean.ConclusionIn summary, our comprehensive analysis offers valuable insights into the evolution and potential functions of GmFRL genes, emphasizing their significance in photoperiodic responses and establishing a foundation for further research on the GmFRL family.